Association between chronic stress-related amygdala metabolic activity and distant metastasis in colorectal cancer - Kim, Hyun Joo; Ha, Sejin; Joung, Chanmin; Kim, Sungeun; Pahk, Kisoo (Frontiers in Endocrinology, 2026)
BackgroundChronic stress has been implicated in cancer progression through neuroendocrine and inflammatory pathways, but its role in colorectal cancer (CRC) remains uncertain. The amygdala, a key stress-responsive brain structure, demonstrates measurable metabolic activity on 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and may serve as a surrogate imaging biomarker of chronic stress. This study aimed to investigate whether elevated amygdala metabolic activity (AmygA) is associated with distant metastasis in patients with CRC.Patients and methodsThis study included patients with newly diagnosed CRC who underwent pre-treatment ¹8F-FDG PET/CT and curative-intent surgery between January 2019 and December 2023. AmygA was defined as the ratio of maximum standardized uptake value (SUVmax) of the amygdala to the mean standardized uptake value (SUVmean) of the ipsilateral temporal lobe. Receiver-operating characteristic curve analysis determined the optimal AmygA threshold for predicting distant metastasis, and multivariable logistic regression identified independent predictors.ResultsSeventy-six patients were analyzed, of whom 21 (27.6%) had distant metastasis. AmygA was significantly higher in patients with distant metastasis than in those without (1.17 ± 0.06 vs. 1.08 ± 0.06; p < 0.001). The optimal AmygA cutoff value for predicting distant metastasis was 1.159, yielding 71.4% sensitivity and 89.1% specificity (area under the curve = 0.844; p < 0.001). Univariable analysis identified advanced T stage, lymph node metastasis, elevated AmygA, increased spleen SUVmax, and higher serum tumor marker levels as significant variables. In prespecified parsimonious multivariable logistic regression models with bootstrap internal validation, elevated AmygA (> 1.159) remained independently associated with distant metastasis.ConclusionsElevated amygdala metabolic activity on pre-treatment ¹8F-FDG PET/CT, a surrogate marker of chronic stress, was independently associated with distant metastasis in CRC. AmygA might serve as a novel imaging biomarker for risk stratification and offer insight into stress-related neural mechanisms underlying metastatic progression.